The Trans-European Transport Network (Ten-T): History, Progress and Financing - Boris Bottcher (Communications - Scientific letters of the University of Zilina, 2006)
Summing up, the author, M.E.S. (Master in European Studies) MA (International Relations) Dipl.-Ing. (Transport Sciences), presents the basis of his actual doctor thesis about the international and strategic dimensions of the enlargement of the Trans–European Network (TEN) to Russia, the caucasus and Turkey. The article deals with the creation and the development of the TEN–T program of the European Commission. After the description of the history of this program, the progress of the fourteen transport priority projects is shown from the report of the Christophersen group to the European Council in 1994. In addition, the guidelines and the financial rules of the TEN-T are examined, which implemented a regular report from the member states to the Commission. With these data the financial forecast gets more realistic and further amendments about the construction progress could be made. Afterwards, the financing of the infrastructure projects is presented on the basis of the different European, government and private fundings. Finally an outcast is given about the new priority projects of 2004.